Reading Together: Engaging Undergraduate Writers Through an Online Book Club - Perkins, Tanya (KULA)

(untitled) (University of Victoria Libraries, 2022)
This teaching reflection examines how “reading together” was fostered in synchronous and asynchronous online environments in two undergraduate creative writing courses through participation in a virtual book club. In the first course, prior to the pandemic, students had the option of meeting in person or via Zoom while we read Daisy Johnson’s Oedipus Rex retelling, Everything Under, for the book club. In the second course, during the pandemic, students had virtual synchronous and written participation choices while we read together Jessica Anthony’s political satire, Enter the Aardvark, with the author visiting in two sessions. In both cases, the goals were consistent: to get students reading as writers; to foster intrinsic motivation through personal choice; and to satisfy students’ desire for community connection while still accommodating personal schedules and geographical location. A virtual book club lets students read on their own schedule and in their own space, but still share their experience and observations with peers over greater distances (and time zones) than would otherwise be possible.